1997
DOI: 10.1046/j.1365-2249.1997.3641266.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of experimental lupus nephritis by combined administration of anti-CD11a and anti-CD54 antibodies

Abstract: SUMMARYMice with chronic graft-versus-host disease (GVHD), induced by injection of DBA/2 lymphocytes in (C57BL10*DBA/2) F 1 hybrids, develop a syndrome resembling systemic lupus erythematosus (SLE) with immune complex glomerulonephritis. In this model we evaluated the role of interactions between CD11a (LFA-1a) and CD54 (intercellular adhesion molecule-1 (ICAM-1)) molecules on leucocytes in the development of renal disease in systemic autoimmunity. Two weeks after induction of GVHD, when anti-nuclear autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Molecules that play a proximate and critical role in controlling tethering (adhesion) and spreading of T cells are integrins such as LFA-1 (CD11a/CD18, ␣ 1 ␀ 1 integrin) (18,19). Blocking of LFA-1 by injection of mice with mAb against LFA-1 in vivo has been described to prevent fetal rejection (20), to reduce the severity of graft-vs-host reactions (21), to prolong allograft survival (22), to inhibit the development of autoimmunity (23), and to block neuropeptide substance P-induced leukocyte migration (24). The latter observation is particularly striking because our previous findings revealed that the lack of immune tolerance, similar to graft-vs-host reactions, is mediated via substance P in stress-triggered murine pregnancy failure (25).…”
mentioning
confidence: 99%
“…Molecules that play a proximate and critical role in controlling tethering (adhesion) and spreading of T cells are integrins such as LFA-1 (CD11a/CD18, ␣ 1 ␀ 1 integrin) (18,19). Blocking of LFA-1 by injection of mice with mAb against LFA-1 in vivo has been described to prevent fetal rejection (20), to reduce the severity of graft-vs-host reactions (21), to prolong allograft survival (22), to inhibit the development of autoimmunity (23), and to block neuropeptide substance P-induced leukocyte migration (24). The latter observation is particularly striking because our previous findings revealed that the lack of immune tolerance, similar to graft-vs-host reactions, is mediated via substance P in stress-triggered murine pregnancy failure (25).…”
mentioning
confidence: 99%
“…Because the cross talk between co-stimulatory molecules on APCs, such as ICAM-1, and the respective ligand LFA-1 on leukocytes is crucial in inflammatory settings, 21,[23][24][25][26]49 we analyzed the phenotype of APC clusters in the skin in response to LFA-1/ICAM-1 blockade. As depicted in Figure 3, C and D, such blockade of ICAM-1/LFA-1 cross talk significantly abolished the stress-induced increase of cell clusters expressing the DC maturation markers MHC II and ICAM-1.…”
Section: Blocking Of Lfa-1/icam-1 Cross Talk Affects the Phenotype Ofmentioning
confidence: 99%
“…21,22 Blocking of LFA-1/ICAM-1 in mice in vivo can abrogate the onset of inflammation, hereby preventing fetal rejection. 23 Moreover, LFA-1/ICAM-1 interactions also are important during graft-versus-host reactions, 24 the development of autoimmunity, 25 and neuropeptide SP-induced leukocyte migration. 26 The latter observation is particularly striking since we were recently able to show that stress leads to neurogenic inflammation in murine skin, comprised of sprouting nerve fibers, increased number and activation of MHC II Ï© APCs and mast cells, upregulation of nerve growth factor, and the neuronal plasticity of dorsal root ganglia toward an increased presence of SP Ï© neurons.…”
mentioning
confidence: 99%
“…Combined administration of anti-LFA-1 and anti-ICAM-1 antibodies was reported to attenuate the development of histological changes in experimental lupus nephritis [26]. In human GN, Canton et al [27]reported that de novo mesangial expression of ICAM-1 in primary focal segmental glomerulosclerosis was a marker for activation of mesangial cells, possibly associated with local cytokine release.…”
Section: Leukocyte Integrins and Glomerular Leukocyte Infiltrationmentioning
confidence: 99%
“…ICAM-1 is mainly expressed on the endothelial cells of peritubular venules, on interstitial mononuclear cells and sometimes on the luminal side of tubular epithelial cells [26, 27, 28, 60, 61, 62]. Tubulointerstitial injury and interstitial leukocyte influx were reported to be significantly milder in nephrotoxic nephritis in ICAM-1 knockout mice than in nephritic control mice [63].…”
Section: Leukocyte Integrins and Interstitial Injurymentioning
confidence: 99%